Subjunctive introduced by verbs and the problem of “subordinating clauses” (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
Attempting to explain when a subjunctive should be used in subordinating noun clauses is always a problem in an SSL class since they do not behave in the same way as other subordinate clauses which, in spite of having a great variety of uses, are very well defined thanks in part to the fact that their classification is based on their syntactic function and not on a classification of verbs based on semantics. For this reason, in this article we will attempt to provide a new perspective to the study of these clauses, paying attention to their function and behavior, and not to the meaning of the verb that introduces them, all in search of a workable systematization for students and teachers of Spanish.
Keywords: subjunctive; subordinating noun clauses; classification; SSL